Advances in accounting behavioral research - Karim, Khondkar E. (Emerald Publishing Limited, 2024)
Focusing on research that examines both individual and organizational behavior relative to accounting, Advances in Accounting Behavioral Research provides an in-depth analysis and exchange of peer-reviewed knowledge across all areas of accounting behavioral research and the development, discussion, and expansion of theories from psychology, sociology, and related disciplines. The chapters collected in Volume 27 include Budgetary Participation, Family Business Environment and Auditor Judgment, CSR as Insurance, IRS Job Characteristics Model, Early Job Attainment of Accounting Majors, Fairness in Cost Allocation and Work of Special Agents of the IRS Using the Job Characteristics Model.
Keywords: Accounting -- Research.; Organizational behavior -- Research.; Financial statements -- Research.; Business & Economics -- Accounting -- Financial.; Financial reporting, financial statements.; Financial accounting.; elektronické knihy; electronic books